2022
DOI: 10.1116/6.0002292
|View full text |Cite
|
Sign up to set email alerts
|

Target ion and neutral spread in high power impulse magnetron sputtering

Abstract: In magnetron sputtering, only a fraction of the sputtered target material leaving the ionization region is directed toward the substrate. This fraction may be different for ions and neutrals of the target material as the neutrals and ions can exhibit a different spread as they travel from the target surface toward the substrate. This difference can be significant in high power impulse magnetron sputtering (HiPIMS) where a substantial fraction of the sputtered material is known to be ionized. Geometrical factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Working gas rarefaction is therefore expected to be less pronounced when modeling with volume average models compared to DSMC simulations. Furthermore, Kozák and Lazar [44] point out that volume-averaged models do not take into account the spatial distribution of the neutral Ar and M densities, and therefore the velocity and angular distribution of the sputtered atoms [71,72], and secondary M-Ar and Ar-Ar collisions are neglected. The latter is justified by a mean free path of a few tens of mm as discussed in section 2.1 and given the extension of the IR it means that only a single collision occurs.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Working gas rarefaction is therefore expected to be less pronounced when modeling with volume average models compared to DSMC simulations. Furthermore, Kozák and Lazar [44] point out that volume-averaged models do not take into account the spatial distribution of the neutral Ar and M densities, and therefore the velocity and angular distribution of the sputtered atoms [71,72], and secondary M-Ar and Ar-Ar collisions are neglected. The latter is justified by a mean free path of a few tens of mm as discussed in section 2.1 and given the extension of the IR it means that only a single collision occurs.…”
Section: Overviewmentioning
confidence: 99%
“…As the magnet configuration was varied, the deposition rate and the ionized flux fraction was determined, while maintaining fixed averaged power by varying the repetition frequency as either the discharge current or discharge voltage was kept fixed. The titanium target was 100 mm in diameter, the working gas pressure 1 Pa, and the average power 300 W. These discharges have been analyzed extensively in order to gain understanding on how the magnetic field strength and topology influence the discharge parameters and operation, including the ionization probability [9], the deposition rate and ionized flux fraction [11,79,80], the size of the IR [70], and transport parameters for both ions and neutrals [72], as well as modeling by the IRM [51] and DSMC simulations [45] to determine the ionization and the target ion back-attraction probabilities. The IRM studies showed that the back-attraction probability is high > 0.8 [51].…”
Section: Titanium Targetmentioning
confidence: 99%
“…The magnet configurations explored here were the same as in the experimental work of Hajihoseini et al [44], where the ionized flux fraction and deposition rate was reported for the various magnet configurations, while keeping the average power constant, by either maintaining fixed discharge voltage or fixed peak discharge current. The discharges explored by Hajihoseini et al have been studied extensively, including exploring the influence of magnetic field on the discharge current, the electron density and the ionization probability [35], to determine the transport parameters of the neutrals and ions of the sputtered species [59], as well as demonstrate how to minimize variations of the flux parameters, the deposition rate and the ionized flux fraction, as the target erodes [45]. The size of the IR is an input parameter when modeling the HiPIMS discharge, using models such as the IR model [26,27].…”
Section: Ir Modelsmentioning
confidence: 99%
“…The two most important parameters are the target atom ionisation probability α t , which describes the likelihood of a sputtered atom being ionised, and the target ion back-attraction probability β t , which is the likelihood that an ionised target ion cannot escape the cathode potential fall and is accelerated back to the target. Since the spatial distribution of ions and neutrals is generally not the same, an additional parameter ξ tn, HiPIMS /ξ ti, HiPIMS , the ratio of the neutral and ion transport parameters [57], is needed to describe the ionised flux fraction [56]…”
Section: Data Availability Statementmentioning
confidence: 99%